Young HIV-Infected Children and Their Adult Caregivers Prefer Tablets to Syrup Antiretroviral Medications in Africa - Nahirya-Ntege, Patricia; Cook, Adrian; Opilo, Wilfred; Namuddu, Rachel; Katuramu, Richard; Tezikyabbiri, Jessica; Naidoo-James, Bethany; Gibb, Diana (PLoS One, 2012)
Provision of anti-retroviral therapy (ART) for HIV-infected children is complicated using syrup formulations, which are costlier than tablets, harder to transport and store and difficult for health-workers to prescribe and caregivers to administer. Dispersible/crushable tablets may be more appropriate. We studied the acceptability of syrups and scored tablets among young children who used both in the AntiRetroviral Research fOr Watoto (ARROW) trial.
Keywords: HIV; Children; Adult Caregivers; Tablets; Syrup Antiretroviral Medications